ANALYSIS THE EFFECTIVENESS OF SUPPLIERS SELECTION OF RAW MATERIAL OF CONCRETE IN INDUSTRY WITH CASE STUDY OF PT MODERNA TEHNIK PERKASA - David Rivaldy Hermanto; Fransiskus Xaverius Viorentino; Liem Gai Sin (AIBPM Publisher, 2018)
The research analyses the effectiveness of supplier selection system in PT. ModernaTehnikPerkasa which engaged in the production of concrete. The research is very important for the company as raw materials is a important part from the production process thus it effects on the production of concrete. As the current system was not analyzedtherefore, this research intends to do the analysis. This research uses interview method as a technique in data collection and using qualitative method to analyses the data. Keywords: PT. Moderna Tehnik Perkasa, concrete, reliable suppliers,competitiveness